Assessment of geological resource potential for compressed air energy storage in global electricity supply. (1st August 2018) - Aghahosseini, Arman; Breyer, Christian
Graphical abstract: The purpose of this study is to evaluate the geological resource potential of compressed air energy storage (CAES) globally. Our research shows that CAES can help solve the intermittency of renewable energy and provide flexibility to the power system due to high geological potential available worldwide. Highlights: The geological resource potential of compressed air energy storage is estimated. Suitable area are determined for the world by overlapping geological formations. Geographic information system is used as a base tool for topographical analysis. North America and Sub-Saharan Africa have the highest shares globally. Northeast and Southeast Asia have the least potential for compressed air storage. Abstract: This paper presents the geological resource potential of the compressed air energy storage (CAES) technology worldwide by overlaying suitable geological formations, salt deposits and aquifers. For this study, the world is divided into 145 regions, which are aggregated to 9 major regions. The potential of CAES in each region is assessed and a relevant map is provided. Three constraints have been implemented, allowing for 1%, 5% and 10% of the selected area to be considered for CAES. Among all major regions, in the most conservative constraint (1% of the total area), North America is the leader with 0.26% suitability of its total area, followed by Sub-Saharan Africa and South America at 0.20% and 0.19%, respectively. A sensitivity analysis is implemented to evaluate the validity and reliability of the results. Three scenarios are considered: Optimistic, Moderate and Pessimistic. Underground natural gas storage data for the US is used due to freely and publicly available data. The natural gas storage site is assumed to have the same structure as CAES. The sensitivity analysis shows that the accuracy of the findings lie in the range of 66–85% and 63–82%, depending on the scenarios and reservoir types. The results clearly reveal that CAES is a promising energy storage technology for electricity supply in most of the regions. This research presents the groundwork to identify the untapped potential of CAES, which can be also utilized for the second generation of CAES such as adiabatic CAES and isothermal CAES.